PENINGKATAN DAN PENYERAGAMAN KUALITAS BATU KAPUR OLAHAN DENGAN APLIKASI RANCANGAN KOKOH TAGUCHI - Leksono, Eko Budi (Department Industrial Engineering, University of Muhammadiyah Malang, 2007)
The problem of quality is often found in limestone combustion of small and medium central industry in Manyar Regency, Gresik, in which, the quality of limestone is defected and has high variation of CaO. One of many methods to improve it is by applying Robust Design from Taguchi, them, its result is socialized in a central industry as a reference for those who conduct combustion in producing material. This study found four controlled factors that each of them consists of two levels that can influence the quality of limestone: A) raw material (level 1 = yellow limestone; level 2 = white limestone); B) Combustion material (level 1 = wood & rubber; level 2 = wood and gerbage sawmill); C) Combustion length of time (level 1= five days; level 2 = four days); D) Combustion temperature (level 1 = ± 800° C; Level 2: ± 875° C). Meanwhile, the optimal combination factor level to improve the quality of limestone is A2, C1, D1, and B2. If factor of combination level is applied, the number of defected good in each combustion can be predicted as much as 1,41% and the defected variable among combustion is 0.37%.